12 Questions about Psychoanalysis - Alenka Zupančič; Marcus Coelen; Jamieson Webster; Jean-Luc Nancy; Federico Leoni; Dany Nobus; Sergio Benvenuto; Alan Bass; Luciano De Fiore (EJP import test, 2018)
None